Metal-directed assembly of large dinuclear copper(II) dithiocarbamate macrocyclic complexes - Cookson, J; Evans, E; Maher, J; Serpell, C; Paul, R; Cowley, A; Drew, M; Beer, P (2010)
The synthesis of a range of dinuclear Cu(II) dithiocarbamate (dtc)-based macrocycles and their characterisation are described. By carefully tuning the size of the aromatic spacer, cavities of different dimensions can be designed. The length and flexibility of the chosen spacer group dictates the intermetallic distance and hence the degree of communication between the two metal centres as evidenced by electrochemical and EPR experiments. This is illustrated by crystallographic evidence that show the macrocycles can host guests (such as CH2Cl2) or can fold and form unexpected Cu(I) dtc clusters. © 2009 Elsevier B.V. All rights reserved.